Genome-wide association study for hereditary ataxia in the Parson Russell Terrier and DNA-testing for ataxia-associated mutations in the Parson and Jack Russell Terrier. Issue 1 (December 2016) - Gast, Alana; Metzger, Julia; Tipold, Andrea; Distl, Ottmar
Abstract Background Spinocerebellar ataxia also referred to as hereditary ataxia comprises different forms of progressive neurodegenerative diseases. A complex mode of inheritance was most likely in Parson Russell Terriers (PRT) and in Jack Russell Terriers (JRT). Recently, the missense mutationKCNJ10: c.627C > G was shown to be associated with the spinocerebellar ataxia (SCA) in JRT and related Russell group of terriers, whereas the missense mutationCAPN1: c.344G > A was associated with late onset ataxia (LOA) in PRT. Results We performed a genome-wide association study (GWAS) in PRT including 15 cases and 29 controls and found a statistically strong signal in the genomic region on dog chromosome 38 (CFA38) whereKCNJ10 is located. We tested theCAPN1: c.344G > A andKCNJ10: c.627C > G (Transcript XM_545752.4) mutations in a sample of 77 PRT and 9 JRT from Germany as well as further 179 controls from 20 different dog breeds. All cases and controls genotyped carried the wild-type for theCAPN1: c.344G > A mutation. Among the PRT, 17/77 (22.1 %) dogs were homozygous for the mutantKCNJ10 allele and 22/77 (28.6 %) dogs were heterozygous. Three cases of PRT had the homozygousKCNJ10 wild-type. In JRT, 1/3 cases did show the mutantKCNJ10 allele homozygous. Thus, we sequenced theKCNJ10 exons with their adjacent regions from 10 PRT and 3 JRT including the animals with imperfect co-segregation of the c.627C > G mutation. We identified a total of 45 genetic variants withinKCNJ10 . The most likely variant explaining the cases appeared a 1-bp-insertion in a C-stretch within exon 3 (KCNJ10: g.22141027insC). In silico analysis showed that this indel may influence the regulation of gene expression. Conclusions In the present study, 16/21 cases of hereditary ataxia perfectly co-segregated with theKCNJ10: c.627C > G mutation. TheCAPN1: c.344G > A mutation could not be validated and seems to be a rare variant in the samples screened. ScreeningKCNJ10 for further mutations did result in a genetic variant explaining 2 JRT cases but further 3 cases with a non-mutant homozygous c.627C > G genotype could not be resolved. Breeders have to be aware that DNA-testing for hereditary ataxia in PRT and JRT does not capture all cases of hereditary ataxia in these dog breeds. At least one further form of hereditary ataxia not yet resolved by a mutation may occur in PRT and JRT.